(untitled) (Journal of Pakistan Orthopaedic Association, 2024)
ABSTRACT Background: Low back pain (LBP) is a leading cause of disability worldwide. The objective of this study was assessment of risk factors of low backache in patients presenting to a tertiary care hospital. Methods: This cross sectional study was conducted for year 2023 in Department of Orthopedics, DHQ Hospital, . A sample of 180 was calculated. Patients with low backache were selected excluding those with malignancy. Demographic and research variables were noted down using structured questionnaire. Pain, disability and depression was assessed using Numerical Rating Pain Scale (NRS), Quebec Disability Index (QDI) and Patient Health Questionnaire-9 (PHQ-9) respectively. Results: Out of 180 patients,153(85%) were married & had chronic LBP, 147(81.67%) lacking exercise, 135(75%) used soft sleeping material, 117(65%) had low income & radiating pain, 108(60%) were female, 93(51.66%) patients work 6-12 hours/day, had trauma history & sitting posture, 87(48.33%) had spinal deformity, 84(46.67%) had age <40 years, 81(45%) had moderately active job & high BMI, 75(41.67%) had 1-5 children, 60(33.33%) were uneducated & degenerative spine, 39(21.67%) spinal injection, 24(13.33%) smokers, 21(11.67%) spinal surgery and 15(8.33%) hypertensive. Severe pain was present in 102(56.67%), severe disability in 69(38.33%) and mild depression in 96(53.34%) patients when assessed on NRS, QDI and PHQ-9 scale respectively. Conclusion: Low backache is caused by many factors. Lack of regular exercise, use of soft sleeping material, in-appropriate sitting posture and high BMI can be addressed by early education of patients and work related ergonomics